Pentingnya Wawasan Teknologi bagi Profesional BK di Era Pendidikan 4.0 - M. Fadlan Choiri; Yarmis Syukur; Dina Sukma (CV. ITTC INDONESIA, 2024)
The Industrial Revolution 4.0 has brought significant transformations in various aspects of life, including education. The Education 4.0 era demands that guidance and counseling (GC) professionals master technological skills to provide effective, efficient, and relevant services according to students' needs. This study aims to analyze the role of technology in enhancing the professional competence of GC teachers and the challenges they face in the digital era. Using a literature review method, this research examines various sources such as scientific journals, articles, and relevant books. The findings indicate that mastery of information technology by GC teachers can improve service effectiveness, facilitate access to counseling, and assist in addressing increasingly complex student issues. However, challenges such as low technology literacy, resistance to change, and the need for professional ethical guidelines in utilizing technology remain obstacles to overcome. Through intensive training and continuous professional development, GC teachers are expected to adapt to the demands of Education 4.0 to provide optimal services for students.